Peran Ruang Terbuka Hijau dalam Mitigasi Perubahan Iklim di Kota Jambi - Nasywa Rahadatul Aisy; Lailal Gusri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Climate change is a global environmental issue that increasingly affects urban areas, including Jambi City. One relevant mitigation solution is the utilization of green open spaces (GOS) as natural carbon sinks. This study aims to examine the role of GOS in climate change mitigation in Jambi City, using the buffer zone of Pondok Meja Village as a case study. A descriptive qualitative method was employed through literature review and short interviews with local residents. The findings show that GOS coverage in Jambi City remains limited at approximately 14.7% of the total city area, thus insufficient to effectively absorb carbon emissions. Pondok Meja Village possesses significant ecological potential, with green areas capable of absorbing up to 142 tons of CO₂ annually if optimally managed. However, GOS management faces challenges such as land-use change, weak policy protection, and low public awareness. Strengthening strategies are needed through spatial planning integration, conservation incentives, and active community involvement. This study recommends a community-based climate change mitigation model that can be replicated in other urban buffer areas.